The Development of an Educational Mobile and Desktop Application for Malaysian Sign Language - Faihana Neesa; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2021)
Due to the Covid-19 pandemic, hearing-impaired children experience challenges in learning and practicing sign languages due to the lack of educational services and learning resources available. This project targets to create educational mobile and desktop applications to aid deaf children in learning Malaysian Sign Language (BIM). The study was conducted through research-based and interview sessions with subject matter expertise. Teachers suggested that online learning is the most suitable platform in order to teach students in the current situation. Therefore, the proposed application was created in order to help the deaf children learn sign language better at home.